Teachers’ Perspectives on Interactive Digital Books for Early Childhood Earthquake Mitigation Education - Sulistyowati, Winda; Kurniati, Euis; Justicia, Risty (Cetta: Jurnal Ilmu Pendidikan, 2025)
This research is motivated by the lack of disaster mitigation education due to teachers' difficulties in conveying abstract disaster-related concepts in early childhood education. However, earthquake disaster mitigation education is crucial for children. This study aims to explore teachers' perspectives on the concept and urgency of disaster mitigation education, analyze teachers' views on the potential of interactive digital books for disaster mitigation, and identify challenges faced during the implementation of interactive digital book media in earthquake disaster mitigation education. This research employs a qualitative method with a case study design. The research subjects were teachers from Elhafa Plus Kindergarten, and data were collected through in-depth interviews, observations, and documentation. The research findings indicate that teachers explicitly emphasize the importance of disaster mitigation education in kindergarten to foster disaster preparedness in children. The implementation of interactive digital books yielded satisfactory results, with teachers rating as high as 90% that this interactive digital book is highly suitable for use in earthquake mitigation education in kindergarten. Teachers selected the photo-together feature as the most attention-grabbing feature because children are engaged in role-playing as if an earthquake is occurring. The challenges faced by teachers in implementing interactive digital book media include the need for digital devices with large screens like Smart TVs so that all children can see clearly and the challenge of managing children's tremendous enthusiasm for using technology such as this interactive digital book media.